Case Report: Alpelisib-Induced Drug Reaction With Eosinophilia and Systemic Symptoms: A Rare Manifestation of a Common Side Effect - Majeed, Umair; Puiu, Tudor; Sluzevich, Jason; Reynolds, Gina; Acampora, Marites; Moreno-Aspitia, Alvaro; Bodiford, Katherine J.; Advani, Pooja (Frontiers in Oncology, 2021)
Alpelisib is a PIK3a inhibitor approved for the treatment of metastatic ER+ breast cancer in combination with fulvestrant. Although rash is a common side effect of this medication, we present the first case of drug reaction with eosinophilia and systemic symptoms (DRESS) upon initial exposure to alpelisib. Here we describe the clinical-pathological findings and management of our patient with alpelisib induced life-threatening DRESS syndrome. The goal of this case report is to highlight association of alpelisib with DRESS syndrome, in clinical practice, so that alpelisib can be immediately stopped and treatment for this serious condition promptly initiated.